ASIMETRI INFORMASI DAN DEBT COVENANT MEMODERASI PENGARUH MANAJEMEN LABA TERHADAP RETURN SAHAM (Studi pada Perusahaan yang Melakukan Initial Public Offering di Bursa Efek Indonesia Periode 2013 - 2016) - Mufidah, Anbar Nisrina; Triyanto, Dedik Nur (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan dan Akuntansi, 2018)
The purpose of this study to determine the effect of earnings management on stock returns and know information asymmetry and debt covenant in moderating the effect of earnings management on stock returns. This research is a descriptive verification research that is causality. The unit of analysis in this study is a company that conducted an IPO in 2013-2016. The research data using sample data selected through purposive sampling technique and obtained by 46 companies doing IPO period 2013 until 2016. This research use technique of simple linier regression analysis and moderated regression analysis. Modified Jones Model is used to detect earnings management. Cummulative Abnormal Return (CAR) is used as a proxy of stock returns. Deb to Equity Ratio (DER) as a proxy for identifying debt covenant. The result of research with simple linear regression test showed that earnings management did not have an effect on stock return. The result of research by using moderated regression analysis test shows that information asymmetry can not moderate the influence of earnings management on stock return. Debt Covenant can moderate the effect of earnings management on stock returns.Keywords: IPO, earnings management, stock return, information asymmetry, debt covenat.